Changes in the education system and modern skills (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Transformations in education and the cultivation of modern skills are vital for updating educational practices globally. The integration of new technologies, digital resources, and innovative teaching methodologies is enhancing the quality of education. Essential modern skills, including critical thinking, problem-solving, and effective communication, are enabling students to thrive in the professional world. These advancements are beneficial not only for students but also for educators and educational institutions. It is crucial that the evolving demands of the education system build upon traditional methods to equip future generations for success in the contemporary job market.